A high cholesterol diet accelerates Alzheimer's progression by promoting fibrotic damage in rats - Ashmita Das; Durlav Chowdhury; Dilip Sharma; Rahul Manna; Surendra H. Bodakhe (Brain Disorders)
The literature documents the ability of oxysterols and TGFβ to cause fibrotic damage in the brain. Our study explores the potential mechanisms of oxysterol interactions with fibrotic mediators in Alzheimer's disease. It focuses on peripherally formed oxysterols and their effects on TGFβ hyperactivation in an experimental rodent model of Alzheimer's disease. We fed experimental rats a high-cholesterol diet for eight weeks and evaluated their cognitive abilities weekly using Hebb's Williams and Radial arm mazes. Using ELISA, we measured plasma and brain oxysterols, transforming growth factor β, amyloid β, matrix metalloproteinase-9, claudin-5, and ATP Binding Cassette Transporter A1 expressions biweekly. The concentrations high density lipoprotein, low density lipoprotein, aspartate aminotransferase, and alanine transaminase were assessed using diagnostic kits, while the antioxidant profile was determined using UV spectroscopy. Our results indicated a synergistic increase in oxysterols, transforming growth factor β, amyloid β, matrix metalloproteinase-9, low density lipoprotein, aspartate aminotransferase, and alanine transaminase, with a concomitant decrease in the experimental animals' Claudin-5, ATP Binding Cassette Transporter A1, high density lipoprotein and antioxidant regulations. These findings suggest that a high-cholesterol diet may lead to oxysterol buildup, resulting in amyloid β accumulation due to transforming growth factor β hyperactivation. In conclusion, our study highlights the need to explore the role of oxysterols in the pathogenesis of Alzheimer's disease. By uncovering potential mechanisms underlying the interplay of oxysterols with fibrotic mediators, our study may pave the way for developing novel therapeutic approaches to manage Alzheimer's disease.